1989
DOI: 10.1099/00221287-135-1-85
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Surface-exposed Epitopes on Chlamydia trachomatis by Immune Electron Microscopy

Abstract: The cell surfaces of two Chlamydia trachomatis serovars were explored by immune electron microscopy with monoclonal anti bodies that recognize a number of chlamydial outermembrane components. Species, subspecies and serovar-reactive epitopes on the major outermembrane protein (MOMP) of a lymphogranuloma venereum biovar strain, L2/434/Bu, and a trachoma biovar strain, F/UW-6/Cx, were exposed on the surfaces of both elementary bodies (EBs) and reticulate bodies (RBs). Three epitopes on MOMP were inaccessible on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
0
32
1
Order By: Relevance
“…The same patterns held for the SDS-61 kDa immunogen. The analogue of the latter protein has been shown not to be surface exposed in C. trachomatis strains (Collett et al, 1989), even though it frequently induces a prominent humoral response in genital infection in humans (Newhall et al, 1982) and guinea-pigs (Batteiger & Rank, 1987). In contrast, the OGP-MOMP elicited strong antibody responses both in immunoblot and in EIA, and elicited marginally more vigorous blastogenic responses.…”
Section: Discussionmentioning
confidence: 99%
“…The same patterns held for the SDS-61 kDa immunogen. The analogue of the latter protein has been shown not to be surface exposed in C. trachomatis strains (Collett et al, 1989), even though it frequently induces a prominent humoral response in genital infection in humans (Newhall et al, 1982) and guinea-pigs (Batteiger & Rank, 1987). In contrast, the OGP-MOMP elicited strong antibody responses both in immunoblot and in EIA, and elicited marginally more vigorous blastogenic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Since outer membrane components and surface antigen expression of C trachomatis change during the development cycle (23)(24)(25)(26)(27)(28), panels of primary antibodies against the L2 strain were used to detect chlamydial particles by IEM. These antibodies were 1) murine monoclonal antibody to chlamydial LPS (LPSMAb), 2) goat polyclonal antibody to chlamydial MOMP (MOMP-PAb) (both of these antibodies were provided by Dr. Whittum-Hudson), and 3) purified goat antibodies to all EB antigens of C trachomatis (EB-Ab; Biodesign International, Kennebunk, ME).…”
Section: Methodsmentioning
confidence: 99%
“…Birkelund et al (2) showed that anti-LPS MAbs bound strongly on the surface of formalin-fixed EB and that LPS readily dissociated from the surface of unfixed EBs. In contrast, Collett et al (9) did not detect the LPS antigen on the surfaces of C. trachomatis EB particles using anti-LPS MAbs and suggested that the LPS moiety was not exposed on the EB surface. This confusion, as to the localization of the LPS moiety on the EB surface, might be due to different MAbs used.…”
Section: Discussionmentioning
confidence: 96%
“…Immunofluorescent assay, peroxidase-and ferritinlabeled immunoelectron microscopy have been used for this purpose (8,17,19). In recent years, the immunogold-labeling method for electron microscopy has been applied to antigenic analysis of the surface of C. trachomatis as well as to that of other micro-organisms (2,9,12). Kuo and Chi (12) and Collett et al (9) examined the surface distribution of epitopes in C. trachomatis using several MAbs, and Birkelund et al (2) examined lipopolysaccharide (LPS) distribution on the C. trachomatis EB surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation